Tranexamic Acid In Prehospital Settings: A Review Of Efficacy, Safety, And Implementation Strategies (The Review of Diabetic Studies, 2025)
Severe hemorrhage remains one of the leading causes of preventable mortality in trauma and emergency medicine. Early administration of tranexamic acid (TXA), an antifibrinolytic agent, has demonstrated effectiveness in reducing mortality when administered promptly. Increasingly, attention has turned toward prehospital TXA administration by emergency medical services (EMS) to optimize outcomes during the “golden hour.” This review synthesizes current evidence on the efficacy, safety, and implementation strategies of TXA use in prehospital settings. Randomized controlled trials, observational studies, and systematic reviews are analyzed to assess patient survival, reduction in bleeding complications, and potential adverse events. The review also highlights barriers such as dosing protocols, training requirements, logistical limitations, and variable guideline adoption across different regions. Furthermore, it explores safety considerations, including thromboembolic risks and patient selection criteria. Conceptual models are presented to guide policy development and optimize integration of TXA into emergency medical services. The findings indicate that prehospital TXA is generally safe and associated with improved outcomes when administered early, though challenges remain regarding widespread adoption and standardization. Recommendations for future research, policy, and practice are proposed.